Zakat–Waqf Synergy in Islamic Social Finance: The Indonesian Model and Sustainable Development - Minati Maulida; Ubaidillah Ubaidillah; Hanik Rosyidah (Cyber Media Indonesia, 2026)
This article analyzes the synergy between zakat and waqf within the framework of Islamic Social Finance (ISF) in Indonesia as a human-centered and value-based model of sustainable development. Departing from fragmented Islamic philanthropy approaches, this study positions zakat and waqf as complementary instruments within a unified social finance ecosystem: zakat functions as a short-term redistributive mechanism to maintain livelihoods and social justice, while waqf provides long-term social financing through productive asset management. Using a descriptive qualitative approach based on literature review and policy analysis, this study examines maqāṣid al-sharī‘ah, ISF practices, and their integration with the Sustainable Development Goals (SDGs). The findings show that the effectiveness of zakat–waqf synergy in Indonesia is shaped not only by institutional structures but also by local wisdom, including mutual cooperation, mosques, Islamic boarding schools, and community philanthropy traditions as forms of social capital. This synergy strengthens ISF as a pillar of sustainable, inclusive, and equitable Islamic development. This article contributes by formulating a conceptual framework for zakat–waqf synergy grounded in maqāṣid al-sharī‘ah and Indonesian local wisdom, offering relevance both for the national context and as a reference model for other Muslim societies.